EFFECT OF THE QUENCHING IN WATER OF THE CEMENTITIOUS MATERIALS SUBJECTED TO FIRE - MESSAOUDENE, IBRAHIM; MOLEZ, LAURENT; JAUBERTHIE, RAOUL; KESSAL, OUSSAMA; SLAMA, LAHCENE (Courrier du Savoir; Vol. 20 (2015): COURRIER DU SAVOIR, 2016)
Many studies have permitted the analysis of the mechanical behavior of concrete subjected to high temperatures. However, no one has done any work on the effect of re-humidification of cementitious materials exposed to a real fire. This is the first study.  To better simulate the effects of a real fire, a test with wood fire is developed. Different cementitious materials (hardened cement pastes, and mortar) are subject to this heating for 1hour. The results of tests indicate that: The average resistance loss is in the order of 60% after exhibition in fire. The re-humidification (sudden quenching in water) allowed a recovery of mass about 10% and consequently a gain of compressive strength about 40%. Internal micro-structure analysis of cement pastes studied by XRD and the observation by a scanning electron microscope (SEM) shows that after the re-humidification, the cement rehydrates again (formation of Portlandite and CSH). Those observations explain the increase mechanical strength.